An Analysis of The Trend of Incidences and Fatality of Pulmonary Tuberculosis in East Java from 2015-2020: A Lesson From COVID-19 - Setyawan, Muhamad Frendy; Mertaniasih , Ni Made; Utomo, Budi; Soedarsono, Soedarsono; Adnyana, I Made Dwi Mertha; Eljatin, Dwinka Syafira; Sumah, Lesty Helda Marsel; Al Karina, Citra; Nuha, Zakiyathun (National Journal of Community Medicine, 2023)
Background: Pulmonary tuberculosis is still a public health problem, and surveillance data analysis has not been done much. Recently a global pandemic of COVID-19 has the potential in disturbing TB elimination programs and treatment. This study aims to comprehensively analyse the incidence rate (IR) and Case Fatality Rate (CFR) of pulmonary tuberculosis in East Java from 2015–2020 and during COVID-19 and the strategies for optimizing tuberculosis disease control. Methodology: The study analyzed annual surveillance data using an analytical descriptive design. The Variables were analyzed with Spearman correlation with a level of evidence of 95% (p<0.05). Results: The prevalence of pulmonary tuberculosis in East Java fluctuated from 2015–2020. In 2020 and during the COVID-19 pandemic, the number of cases and morbidity rates increased. Statistic results confirm the presence of a significant correlation between the values of Incidence rate (IR) and Case Fatality rate (CFR) (p = 0.032), IR and Treatment Success Rate (TSR) (p = 0.020), and CFR and TSR (p = 0.002). Population density is not correlated with the number of new cases (p = 0.667). Treatment rates have increased to 51%; cure and treatment rates have decreased to 76% and 89%, respectively, and there was a 4% increase in mortality during COVID-19. Conclusions: COVID-19 has tremendously affected the treatment of pulmonary TB cases in East Java, Indonesia by increasing the incidence rate and decreasing the fatality rate. The pandemic promotes fear in the community to check their medical status and improve the quality of their health in East Java.